2010
DOI: 10.1039/c0em00046a
|View full text |Cite
|
Sign up to set email alerts
|

Environmental monitoring to enhance comprehension and control of infectious diseases

Abstract: In a world of emerging and resurging infectious diseases, dominated by zoonoses, environmental monitoring plays a vital role in our understanding their dynamics and their spillover to humans. Here, we critically review the ecology, epidemiology and need for monitoring of a variety of directly transmitted (Sin Nombre virus, Avian Influenza) and vector-borne (Ross River virus, West Nile virus, Lyme disease, anaplasmosis and babesiosis) zoonoses. We focus on the valuable role that existing monitoring plays in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 82 publications
(151 reference statements)
0
35
0
Order By: Relevance
“…This finding has important implications for exposure risk to SNV. If human exposure is a function of the amount of SNV shed into the environment, the amount of particulate exposure (Carver et al 2010) and persistence of virus in the environment (Kallio et al 2006), then simply moving around in buildings (which is more common than sweeping) may pose a significantly greater infection risk than sweeping. We acknowledge that this result appears counterintuitive, because sweeping produces a visually greater amount of particulates, and other studies suggest sweeping may be an important determinant of human exposure to SNV (Armstrong et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has important implications for exposure risk to SNV. If human exposure is a function of the amount of SNV shed into the environment, the amount of particulate exposure (Carver et al 2010) and persistence of virus in the environment (Kallio et al 2006), then simply moving around in buildings (which is more common than sweeping) may pose a significantly greater infection risk than sweeping. We acknowledge that this result appears counterintuitive, because sweeping produces a visually greater amount of particulates, and other studies suggest sweeping may be an important determinant of human exposure to SNV (Armstrong et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Sweeping or cleaning in peridomestic settings such as barns and outbuildings, could increase human exposure risk to aerosolized particles contaminated with SNV from deer mouse excreta (Armstrong et al 1995; Childs et al 1995b; Zeitz et al 1995). Furthermore, SNV contaminated particulate matter has been hypothesized to survive longer within peridomestic settings because the virus is sheltered from external environmental conditions, such as wind and ultraviolet radiation, that would disperse the contaminated deer mouse excreta and degrade the virus (Carver et al 2010; Gedeon et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…This information could help direct public health intervention strategies and ultimately lead to optimising cost-effectiveness as well as social cost-benefi t of different interventions to reduce health impact. The assessment also showed that basic environmental indicators could be used to identify high-risk locations for leptospirosis infection ( Figure 5) and supported a novel approach of using environmental monitoring to enhance infectious disease surveillance (22) and improve the overall effectiveness of environmental health surveillance and management (21) .…”
Section: Practical Application Of the Fi Ndingsmentioning
confidence: 99%
“…If it was possible to accurately predict disease incidence and prevalence based on environmental indicators, disease surveillance could be complemented by environmental hazard monitoring, which is usually cheaper and logistically simpler, thus providing a more cost-effective surveillance strategy (22). For example, recent studies have shown that leptospirosis hotspots and outbreaks could potentially be predicted using environmental and climate data in the Pacific Islands (17,19).…”
Section: Environmental Monitoringmentioning
confidence: 99%